Studi Perilaku Teritorial Burung Cangak Abu (Ardea cinerea Linn.) di Kebun Raya dan Kebun Binatang Gembiraloka Yogyakarta - Wahyu Nugroho; Djuwantoko Djuwantoko; Wibowo N. Jati (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2005)
This study aim to see on ecological aspect of Cangak Abu specifically on its behavior in defending their terittory. This research was done from July to August 2004. Data collecting was done using territory mapping methods with three observation area (1st-3rd). One pair of Cangak Abu observed at each area. Cangak Abu showed some behavior such as vocalization, sound, visual display, visual display-sound, visual display-sound-shortflight, patroling flight and fighting. The territories on frist to third observation areas were OA : 9 m2; OA : 6 m2 and OA : 9 m2 respectively.